The Rohingyas of Arakan : history and heritage - Siddiquee, Mohammad Mohibullah (Chittagong : Ali Publishing House, 2014)
Origin and history of Rohingyas, a minority, mostly muslim, population of Arakan of Burmah that lies along the eastern coast of Bay of Bengal. Many Rohingyas took refuge in Bangladesh to flee persecution in Burmah.
Keywords: Rohingya (Burmese people) -- History